Percepção da avaliação docente em Instituições de ensino privado no México - Balderas Gutiérrez, Karime Elizabeth (2022)
Teacher evaluation is part of different educational models that, due to its characteristics, becomes a way to identify strengths and weaknesses related to teaching practice. In Mexico, private education institutions carry out the teacher evaluation process under conditions that influence work, personal and professional development aspects. For this reason, the objective of this article is to show the manifestations of perception of teacher evaluation. The question that guided the research was: What is the perception regarding the evaluation of teacher performance and its relationship with continuing professional education?